Diversity Management in Multicultural Environment - Czapran, Tomasz Bronislaw; Dvořáková, Zuzana, 1960-; Kleibl, Jiří; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
The dissertation thesis deals with the issues of diversity management in multicultural environment. The primary objective of the thesis is to create a graphical model of diversity management for multicultural organisations operating in the field of information technology. The secondary objective is to identify, through expert literature research, the current approaches to diversity management and to clarify its benefits. The theme is examined and discussed from theoretical as well as practical point of view. The theoretical part deals with the scope, categories, instruments, models and concepts of diversity, as well as diversity management with equal opportunities in the workplace. This section was created not only on the basis of expert literature, but also on the basis of inputs found in impacted and reviewed journals and articles. The practical part presents the quantitative and qualitative research carried out among managers in 14 selected enterprises applying diversity management in varying degrees. Based on this qualitative research hypotheses are formed. These hypotheses are subsequently verified by the quantitative research conducted among managers of selected companies. The practical part has empirical character, as it investigates a specific level of application of diversity management in selected IT organisations with multicultural environment. This investigation is carried out using quantitative and qualitative data collection.
Vedoucí práce: Zuzana Dvořáková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations